Acute toxicity of selected pesticides on the prawn Penaeus monodon - Joseph, K O; Gupta, B P; Krishnani, K K; Muralidhar, M (Indian Journal of Fisheries, 2011)
Static bioassay tests for acute toxicity of four pesticides on the prawn Penaeusmonodon in brackishwater medium were conducted. The 96 h LC„ values ofpesticides such as DDT, BHC(HCH), heptachlor and endosulfan were foundto be 2.08, 4.10, 16.25 and 2.90 ppb respectively for prawns of size group 33-46 mm. Admissible safe concentration for DDT, BHC, heptachlor andendosulfan were 0.21, 0.41,1.63, 0.29 ppb respectively. LCj,, values were alsocalculated for each time interval and toxicity of the pesticides was comparedusing toxicity curves. Pesticides were not detected in creek and coastal waters.